DISTAL OEDEMA FOLLOWING CIRCUMFERENTIAL SKIN LOSS OF LEGS - Chander Parkash Sawhney (Indian Journal of Plastic Surgery, 1985)
Oedema distal to circumferential skin loss of leg even after skin coverage is very disabling. 12 cases of circumferential skin loss of leg at various levels have been studied. RI131 HSA clearance and NaI131 clearance studies has been carried out in all cases immedialely after skin coverage and at follow up, 6 months to 2 years laler. Venography and lymphangiogmphy were done whether indicated. Lymphatic obstruction was a conslant finding in all patients, irrespective of the site involvement. Venous obstruction is evident only in those with involvement of lower third or whole of the leg or when there is associated deep vein thrombosis. Wearing of continuous external elastic support during ambulation or use of full thickness skin flap bridging the area of skin loss keeps oedema under control.